Thermal Comfort Investigation in UTHM Library and the Influence of Clothing on Adaptive Thermal Comfort - Zaraa Allah Mohammad R. Zaraa Allah, Haslinda Binti Mohamed Kamar, Wong Keng Yinn (Design Engineering, 2021)
Researchers and various organizations have devised criteria for the classification of office buildings, although there is no internationally recognized standard. Business managers and property management organizations lead the way. The Building Owners and Managers Association (BOMA) of Canada classified offices into three classes: Class A, Class B, and Class C. These criteria included building age, location, construction, architecture, management, tenants, leasing rate, building systems, elevators, security, environment, and parking. Classifies office buildings based on six parameters: presentation, administration, function, service, access and circulation, and amenities. Building vertical projection and budget were used to classify office buildings in UTHM Library in Malaysia. While these classifications took into consideration cost and aesthetics, they failed to consider ventilation, which plays a major role in determining thermal comfort in the tropical region. The study classified office buildings based on the type of workplaces and the office ventilation systems under consideration of the local context and climate. In the subsections that follow, we discuss these criteria in more detail.